1998
DOI: 10.1007/bf02375941
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical promotion of Pd for the hydrogenation of C2H2

Abstract: Abstract. The effect of Non-Faradaic Electrochemical Modification of Catalytic Activity, or insitu controlled promotion, was investigated during Acetylene selective hydrogenation on Pd films deposited on 13"-A1203, a Na + conductor, at temperatures from 60 to 100 ~ and GHSVs from 103 to 104 h -1, i.e., under conditions similar to those used in industrial processes. It was found that both acetylene conversion and hydrogenation selectivity can be affected by means of externally applied potentials, i.e., by suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 25 publications
1
2
0
1
Order By: Relevance
“…We may ascribe those differences in reactivity to the change in oxidation state of Pd, as reflected by a shift in XPS binding energies of Pd from initially 337.6 eV to 337.1 eV as hydrogen spillover progressed (Figure S11), as well as by Bader charge analysis of PMo 11 O 39 Pd 1 as a function of H coverage (Table S1). This reactivity trend is consistent with previous reports on the drop in C=C bond hydrogenation activity when the oxidation state of Pd was reduced [24] . We further found that a catalyst not exhibiting hydrogen spillover (PW 11 O 39 Pd 1 ) was significantly more active in the hydrogenation of vinyl acetate (Figure S35).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…We may ascribe those differences in reactivity to the change in oxidation state of Pd, as reflected by a shift in XPS binding energies of Pd from initially 337.6 eV to 337.1 eV as hydrogen spillover progressed (Figure S11), as well as by Bader charge analysis of PMo 11 O 39 Pd 1 as a function of H coverage (Table S1). This reactivity trend is consistent with previous reports on the drop in C=C bond hydrogenation activity when the oxidation state of Pd was reduced [24] . We further found that a catalyst not exhibiting hydrogen spillover (PW 11 O 39 Pd 1 ) was significantly more active in the hydrogenation of vinyl acetate (Figure S35).…”
Section: Resultssupporting
confidence: 92%
“…This reactivity trend is consistent with previous reports on the drop in C=C bond hydrogenation activity when the oxidation state of Pd was reduced. [24] We further found that a catalyst not exhibiting hydrogen spillover (PW 11 O 39 Pd 1 ) was significantly more active in the hydrogenation of vinyl acetate (Figure S35).…”
Section: Forschungsartikelmentioning
confidence: 86%
“…While electrochemical promotion has mostly applied to oxidation reactions, there is a plethora of studies on hydrogenation and hydrogenation reactions [1,[28][29][30][31]. Among these studies, CO 2 and CO hydrogenation for the production of alcohols and other oxygenated products appear to be of a considerable technological interest.…”
Section: Perspectives In Hydrogen Production and Utilizationmentioning
confidence: 99%
“…Nasicοn [54], ιόντων Η + όπως CsHSO4 [26] και CaZr0.9In0.1O3-a [55], ιόντων Κ + όπως Κ2ΥΖr(PO4)3 [56] ιόντων Fόπως CaF2 [57] καθώς και μικτοί αγωγοί όπως TiO2 [21] και CeO2 [54]. Εκτός από αντιδράσεις πλήρους ή μερικής οξείδωσης όπου αρχικά εμφανίστηκε το φαινόμενο [2,9], έχουν γίνει μελέτες και σε αντιδράσεις αφυδρογόνωσης [11], υδρογόνωσης [58,59] και διάσπασης [29,56,[60][61][62]. Στον Πίνακα 1.1 παρουσιάζονται συνοπτικά τα καταλυτικά συστήματα που έχουν μελετηθεί με το φαινόμενο NEMCA καθώς και τιμές βασικών παραμέτρων που χαρακτηρίζουν το φαινόμενο αυτό, οι οποίες συνοψίζονται και περιγράφονται στη συνέχεια.…”
Section: πειραματική διάταξηunclassified